Laboratory screening of fungicides using cellulose film and leaf discs against South American leaf blight pathogen, Microcyclus ulei - Chee K H; Darmono T W; Dossantos A F (Journal of Natural Rubber Research, 1986)
Cellulose film coated with fungicide was found to be a suitable replacement of agar medium in laboratory screeninn of fungicides against Microyclus ulei. It revealed the fungicidal, fungistatic and residue effect of the chemical examined. Discs of young Hevea leaves sprayed with a fungicide and inoculated with conidia also gave a good estimate of the effectiveness and curative property of the fungicides. The effectiveness an properties of chlorothalonil, mancozeb, tridemorph, dithianon, benomyl, triforine, triadimefon, ccarbendazim and thiophanate methyl as they related to South American leaf blight control were compared.
Keywords: Fungicides; Microcyclus ulei; SALB